THE ROLE OF SCHOOL TV IN INCREASING PARENTAL PARTICIPATION TO SUPPORT THE LEARNING PROCESS IN PAUD - Diana Indah Palupi; Emma Rahmani; Erlin Yusnita; Dian Farista; Sri Watini (Jurnal Scientia, 2022)
One of the media in this digitalization era that is considered very suitable for the development of early childhood communication skills is school TV by utilizing the "School Stage" feature on the School TV Channel in the form of Streaming Broadcasts. This paper aims to discuss the presence of school TV which is an attraction for early childhood education institutions as an alternative to increasing parental participation to support the learning process in PAUD. This research was conducted using a qualitative descriptive research method. Collecting data with surveys, documentation, and field notes, as well as literature study. The research locations were conducted at 4 early childhood education institutions, namely Taman Hijau Kindergarten in Batam City, Kindergarten 'ABA 72 Bekasi Selatan City, RA Qurrotul'Uyun Bekasi Timur Bekasi City, Kindergarten Islam Inclusion Cahaya Kautsar Jakarta. The results of this study indicate that school TV has a high potential to convey educational messages that attract children's interest and attention and is proven to increase parental participation to be more involved in the learning process. The importance of educational broadcasts on school TV can be used as a source of learning. School TV has many positive impacts, one of which is that it can increase the closeness between parents and teachers and also the more intense communication between parents and children is established.